Pengelolaan Kebun Gizi melalui Program Gerakan Masyarakat Hidup Sehat di Desa Sambung Rejo - Rahmawati, Pudji; El-Basher, Labib Aqil Fawa’iz (Islamic Management and Empowerment Journal, 2026)
This study aims to analyze the management and factors inhibiting the sustainability of nutrition gardens within the Healthy Living Community Movement (GERMAS) program in Sambung Rejo Village, RT 27 RW 04, Mliwis, Cepogo, Boyolali. The method used is a case study with a qualitative approach, data collection was conducted through in-depth interviews and passive participant observation, with purposive sampling and source triangulation techniques to ensure data validity. The results show that the management of nutrition gardens is carried out through the stages of land and planting media preparation, planting and maintenance, and monitoring and evaluation. However, the sustainability of nutrition gardens is hampered by the minimal role of facilitators and the lack of coordination between community institutions, which results in hampered participation and innovation. Therefore, strengthening effective mentoring and coordination of community institutions is needed to increase program effectiveness, support food security, and improve community nutrition sustainably.